THE IMPLEMENTATION OF UNIVERSAL DESIGN FOR LEARNING (UDL) AS AN INCLUSION STRATEGY IN SPECIAL EDUCATION: OVERCOMING THE LOGIC OF INDIVIDUALIZED - de Souza, Thereza D’Ávila Maria Fernandes (Seven Editora, 2026)
Contemporary inclusive education demands a transition from the integration model to a perspective of full inclusion, questioning the effectiveness of reactive curricular adaptations. This study aims to analyze the implementation of Universal Design for Learning (UDL) as a fundamental strategy to replace individualized adaptation practices with a teaching model that is accessible and inclusive from its conception. Methodologically, the research is characterized as a qualitative bibliographic study using a deductive method, based on databases such as SciELO and Google Scholar, with theoretical support from authors such as Zerbato, Pletsch, and Sebastián-Heredero. The results indicate that UDL, grounded in neuroscience and structured around the pillars of engagement, representation, action, and expression, enables the creation of flexible curricula that recognize brain variability as the norm. Unlike a posteriori accommodations, which often stigmatize students with disabilities and reduce learning expectations, universal planning eliminates systemic barriers and promotes the autonomy of all learners. It is concluded that the application of UDL represents a necessary paradigmatic shift, moving the focus from the pathology of the individual to the rigidity of the curriculum. The implementation of this approach requires a reconfiguration of teaching culture and instructional design, transforming the school into a democratically accessible space where diversity is valued as pedagogical potential and equity is organically ensured, consolidating the inalienable right to knowledge for all students.DOI: https://doi.org/10.56238/sevened2026.008-022